Gastrocnemius skeletal muscle microvasculature and neuromuscular junction alterations in mice with experimental acute chagas infection - Lugo de Yarbuh, Ana; Colasante, Cesare; Alarcón, Maritza; Moreno, Elio (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> A light and transmission electron microscopy study was performed in skeletal muscles (SM) Gastrocnemius (G) from mice experimentally infected with Trypanosoma cruzi to determine changes on microvessels (MV) and neuromuscular junction (NMJ) of G. In this study 10 male (mus musculus) (20 g) were infected subcutaneally with 1.104 bloodstream trypomastigotes M/DID/Ve/02/DSM strain. Five mice were kept as uninfected controls. The parasites induced a complete paralysis of the rear limbs and death while still in the acute ChagasÂ´disease. The histopathology of SM showed inflammatory cell infiltration by mononuclear and polymorphonuclear leukocytes associated with marked parasitism in the muscle fibers of G. Indirect immunofluorescence revealed interstitial IgG deposit as bands regularly spaced along the nerve terminals at 40 days postinfection (pi). At this time T. cruzi antigens and intracellular amastigotes nests were also observed. The marked inflammatory response and morphological changes in the SM were confirmed by transmission electron microscopy. Capillary ultrastructure was seen to be altered, with points of cell cytoplasm discontinuity that appear to represent holes in the microvessel walls. This finding coincided with amastigote nests in myofibers, close contacts between trypomastigotes and endothelial cells and marked thickening of the basement membrane of the muscle vessels. Loss of capillary lumen and a process of ischemia also were observed in the SM of infected mice. The neuromuscular junction showed degeneration of intramuscular nerve fibers, reduction in the axon caliber, swollen mitochondrial, increase in the actin filaments and microtubules in the axoplasm, and swelling of the Schwann cells. Increase in the nerve terminal perimeter and most of the synaptic vesicles were localized near the presynaptic active zones and scarces in the axoplasm. At this stage of infection the changes findings in MV and NMJ of G infected with T. cruzi, as well as ischemia and alterations in the presynaptic membrane densities in the active zones, shows that the abnormal mice NMJ is associated with an activity dependent modulation of the neurotransmission, producing abnormal motor activity and paralysis of the rear limbs mice while still in the acute ChagasÂ´disease. Â